Participatory research – some comments on the sources of inspiration of the research method used in the project - Brzeziński, Kamil (Science Communication in Poland. Participation. Dialogue. Trust, 2021)
In recent decades, participation – broadly understood as the inclusion and involvement of citizens in political activities, as well as decision-making processes at various levels – has become an important element in the evolution of democratic systems. Processes in the political sphere that involve citizens in shaping politics and making decisions that are important from their perspective are increasingly observed. In the scientific sphere, one can also notice democratising tendencies, which involve the broader inclusion of respondents in research processes. Therefore, this chapter will discuss ways to conduct research based on participation, which was a valuable source of inspiration for the CONCISE project implementers. The following approaches will be described: 1) deliberation techniques, which involve working out a consensus in a group; 2) participatory action research, supporting the cooperation of researchers and participants – the recipients of the research results; 3) projects in which conclusions are developed with the active participation of respondents, and 4) research initiated and carried out by non-researchers. The chapter also describes the World Wide Views methodology, which is the basis for public consultations carried out under the CONCISE project.